Zinc porphyrin–polydopamine core–shell nanostructures for enhanced photodynamic/photothermal cancer therapy. (1st July 2019) - Ou, Changjin; Zhang, Yewei; Pan, Dong; Ding, Kaikai; Zhang, Shichao; Xu, Wenjing; Wang, Wenjun; Si, Weili; Yang, Zhou; Dong, Xiaochen
Abstract : Zinc porphyrin–polydopamine core–shell nanostructures were constructed for cancer photodynamic/photothermal synergistic therapy. Abstract : Multimodal therapy, integrating two or more compositions with different functions into a nanoplatform, will generate the synergistic effects of the multi-components and effectively improve the tumor therapeutic efficacy. Herein, core–shell structured ZnP@PDA nanoparticles (NPs) were easily constructed via encapsulating the near-infrared (NIR) photosensitizer of zinc porphyrin nanoparticles (ZnP NPs) with polydopamine (PDA). The ZnP@PDA NPs displayed good biocompatibility and could effectively prevent aggregation after intravenous injection. Triggered by a NIR laser, the ZnP@PDA NPs exhibited excellent photodynamic performance. Furthermore, compared with PDA or ZnP NPs, the ZnP@PDA NPs showed improved photothermal performance with a high photothermal conversion efficiency (PCE) of 46.8% due to the triplet exciton quenching and fluorescence resonance energy transfer (FRET). In vitro and in vivo evaluations demonstrated that the ZnP@PDA NPs could directly target the tumor site via the enhanced permeability and retention (EPR) effect and exhibited strong phototoxicity and outstanding tumor phototherapeutic efficacy.